In-parallel connected intermittent hemodialysis through ECMO does not affect hemodynamic parameters derived from transpulmonary thermodilution. (November 2017) - Lahmer, Tobias; Mayr, Ulrich; Rasch, Sebastian; Batres Baires, Gonzalo; Schmid, Roland M.; Huber, Wolfgang
Introduction: We report a case of renal replacement therapy (RRT) during extracorporeal membrane oxygenation (ECMO) via a single venous acce ss and analyze the feasibility of transpulmonary thermodilution (TPTD) for hemodynamic monitoring. Case report: ECMO and RRT connected into the ECMO-extracorporeal circuit were performed via a single venous access because of multiple venous thromboses. An indicator for TPTD and pulse contour analysis (PCA) was applied into the central venous catheter (CVC) placed in the right vena jugularis. TPTD and PCA demonstrated comparable cardiac index. Discussion: Congruent data for TPTD and PCA could be observed during TPTD and PCA measurements before ECMO, after ECMO and during ECMO and RRT. This might be explained by high blood flow having the lowest impact on TPTD by venous drainage in the femoral vein/distal vena cava and the TPTD indicator injection using the jugular CVC, as reported in our case. Conclusion: Hemodynamic monitoring using TPTD and PCA during ECMO/RRT is feasible and provides reliable results.